Answer:
see explanation
Explanation:
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y-intercept )
(a)
here m = -
and c = 6, hence
y = -
x + 6 ← equation of line
(b)
here m = 6, hence
y = 6x + c ← is the partial equation
to find c substitute (2, - 6 ) into the partial equation
- 6 = 12 + c ⇒ c = - 6 - 12 = - 18
y = 6x - 18 ← equation of line
(c)
to calculate m use the gradient formula
m = ( y₂ - y₁ ) / ( x₂ - x₁ )
with (x₁, y₁ ) = (- 1, 3) and (x₂, y₂ ) = (4, 7)
m =
=
, hence
y =
x + c ← is the partial equation
to find c substitute either of the 2 points into the partial equation
using (- 1, 3 ), then
3 = -
+ c → c = 3 +
=
![(19)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m0ge7m09wqe4ih6fxtx5o5uj8l63nzqog3.png)
y =
x +
← equation of line